Analysis of the maternal genome of Elymus nutans from the Qinghai‐Tibet Plateau based on chloroplast genomes. (30th August 2021) - Liu, Ruijuan; Xia, Mingze; Liu, Demei; Jiang, Liling; Shen, Jicheng; Chen, Wenjie
Abstract: Elymus nutans is an important forage and ecological restoration herbage in the Qinghai‐Tibet Plateau, which is an allohexaploid species with the StStYYHH genomes. Previous studies suggested that Pseudoroegneria is the maternal genome donor to E. nutans, but exactly which Pseudoroegneria species is still unknown. Here, we report the complete chloroplast (cp) genome sequence of two E. nutans from the Qinghai‐Tibet and five Pseudoroegneria species. The cp genomes of the seven samples ranged narrowly from 134, 924 bp to 135, 142 bp in size, comprising inverted repeats of 20, 808–20, 814 bp, single‐copy regions of 80, 536–80, 754 bp (LSC) and 12, 762–12, 772 bp (SSC). It encoded 111 total genes, of which 78 protein‐coding genes, 29 tRNA genes, and four rRNA genes. A comparative cp genome analysis and characteristic junctions of St ‐containing species revealed that the gene content and organization were conserved, but differences were still found in sequence variation and border regions. Further, the Bayesian inference (BI) phylogenetic tree using the whole chloroplast genome sequence demonstrated that P. cognata might be the most likely St genome donor of E. nutans in the Qinghai‐Tibet Plateau, followed by P. strigosa . However, whether E. nutans has other maternal genomes still needs further research.